Peningkatan Kesadaran Generasi Muda dalam Penerapan Hygiene Sanitasi di Rumah Asuh YABNI Padang - Sevilla Ukhtil Huvaid; Hanim Khalida Zia (Yayasan Literasi Sains Indonesia, 2023)
Foster home is fostering institution that has a boarding system. Foster children who live in crowded environments with poor sanitation and low personal hygiene are risk factors that can facilitate the emergence of various health problems including infectious diseases. The results of preliminary survey at the YABNI Padang Foster Home show the fact that there are several health problems experienced by foster children, one of which frequently appears is skin disease. According to the management, this occurs due to the low awareness of foster children in implementing healthy behavior both personally and in maintaining a clean environment. The large number of children in foster care with a relatively small number of managers means that health-related guidance and monitoring efforts do not run optimally. The local health center also does not carry out routine visits. The solution offered to overcome this problem is to provide education about the importance of implementing personal hygiene and maintaining environmental sanitation. This education is important to provide to increase understanding and awareness of foster children in order to prevent and minimize the emergence of health problems in the future.